Analisis Frasa Endosentrik pada Tajuk Rencana Surat Kabar Tribun Pekanbaru - Jamilin Tinambunan; Mega Fortuna (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
This research is motivated by endocentric phrases. The problems studied in this study are: How are the coordinating endocentric phrases in the editorial of the December 2020 edition of the Tribun Pekanbaru newspaper? What is the attributive endocentric phrase in the editorial of the December 2020 edition of the Tribun Pekanbaru newspaper? How is the appositive endocentric in the editorial of the December 2020 edition of the Tribun Pekanbaru newspaper? The aims of the study were to identify and describe coordinating endocentric phrases in the editorial of the newspaper Tribun Pekanbaru December 2020 edition, to identify and describe attributive endocentric phrases in the editorial editorials of the newspaper Tribun Pekanbaru December 2020 edition, to identify and describe the appositive endocentric phrases in the editorials of the letter. Newspaper Tribun Pekanbaru December 2020 edition. The research method used is a descriptive method. The research approach carried out by the author uses a qualitative approach. Data collection techniques in this study are documentation techniques, content analysis techniques and documentation. The results of the research are to identify endocentric phrases contained in the editorials of the newspaper Tribun Pekanbaru edition of 1-31 December 2020, classifying endocentric phrases contained in the editorials of the newspaper Tribun Pekanbaru editions of 1-31 December 2020, to analyze the endocentric phrases contained in the editorials of the letters. Newspaper Tribun Pekanbaru edition 1-31 December 2020, Summarizing the endocentric phrases contained in the editorial of the newspaper Tribun Pekanbaru edition December 1-31 2020.